2018
DOI: 10.1001/jamaophthalmol.2018.1544
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lampalizumab for Geographic Atrophy Due to Age-Related Macular Degeneration

Abstract: IMPORTANCE Geographic atrophy (GA) secondary to age-related macular degeneration is a leading cause of visual disability in older individuals. A phase 2 trial suggested that lampalizumab, a selective complement factor D inhibitor, reduced the rate of GA enlargement, warranting phase 3 trials. OBJECTIVE To assess the safety and efficacy of lampalizumab vs sham procedure on enlargement of GA. DESIGN, SETTING, AND PARTICIPANTS Two identically designed phase 3 double-masked, randomized, sham-controlled clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
197
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 295 publications
(205 citation statements)
references
References 41 publications
2
197
1
5
Order By: Relevance
“…First, as individuals age, physiologic changes at the cellular level lead to RPE cell apoptosis (reviewed in Ehrlich et al 42 ), suggesting that patients with AMD may be destined to demonstrate atrophy. Phase 3 clinical trial data from patients with GA and no evidence of MNV demonstrated increased GA lesion size over time 43,44 ; such increases in the absence of VEGF inhibition support atrophy as part of the natural history of AMD. Recent evidence suggests that atrophy can arise de novo in areas of pre-existing subretinal lesions or in areas with outer retinal atrophy alone or with RPE loss.…”
Section: Discussionmentioning
confidence: 95%
“…First, as individuals age, physiologic changes at the cellular level lead to RPE cell apoptosis (reviewed in Ehrlich et al 42 ), suggesting that patients with AMD may be destined to demonstrate atrophy. Phase 3 clinical trial data from patients with GA and no evidence of MNV demonstrated increased GA lesion size over time 43,44 ; such increases in the absence of VEGF inhibition support atrophy as part of the natural history of AMD. Recent evidence suggests that atrophy can arise de novo in areas of pre-existing subretinal lesions or in areas with outer retinal atrophy alone or with RPE loss.…”
Section: Discussionmentioning
confidence: 95%
“…Several examples of unique patterns only seen by DNIRA identify additional or complementary information for monitoring RPE health versus traditional 488 nm autofluorescence imaging. These data highlight an opportunity for superior stratification and earlier detection of pathology such as reversible RPE dysfunction, critical to identifying therapeutic response signals, as has remained problematic for example in studies of geographic atrophy (19).…”
Section: Discussionmentioning
confidence: 99%
“…Microperimetry data were collected as a secondary endpoint in a subset of patients in the lampalizumab clinical program, including the Proxima A (NCT02479386) and Proxima B (NCT02399072) natural history studies of patients with GA, as well as the phase 3 Chroma (NCT02247479) and Spectri (NCT02247531) interventional studies assessing the efficacy and safety of lampalizumab for reducing the rate of GA enlargement. 19 In these clinical trials, predefined study endpoints assessing longitudinal GA progression were the number of absolute scotomatous points and the mean retinal sensitivity.…”
Section: Progression Of Gamentioning
confidence: 99%